A Comparative Study on the Painting Forms of Western Oil Painting and Chinese Ink Painting (American Journal of Arts and Human Science, 2024)
Since modern international students introduced oil painting on a large scale to China, oil painting has been developing in China for over a hundred years. In citing the process of progress, learning, integration, and improvement, the change in titles from “Western painting” and “Western painting” to “oil painting” and then to “Chinese oil painting” indicates that oil painting, as an art form, has deeply embodied the characteristics and connotations of traditional Chinese culture. During this period, its development is closely related to the historical background of the entire China, reflecting the continuation and evolution of traditional Chinese freehand brushwork spirit in the complex and changing context of the times. This article compares oil paintings imported from abroad with domestic ink painting, taking the artistic realm of painting in both the East and the West as the starting point. The main axis that runs through them is Chinese ink painting and Western oil painting landscapes. Showcasing the similarities and differences between Chinese ink wash landscape painting and Western oil painting landscapes, Chinese landscape painting emphasizes the expression of emotions and a sense of awe and emotion towards nature, with the main idea of “learning from nature”; The Western oil painting landscape emphasizes the realism of the scenery, which is a re-creation of nature, allowing people to have a realistic feeling of being there when watching the painting. The main reason there are these differences between Chinese ink painting and Western oil painting landscapes is due to different social and cultural backgrounds and fields of consciousness.